Levels Of Competence Which Are Important In The Professional Activity Of Higher Education Teachers In The Field Of Architecture And Construction In The Process Of Modern Education - Parmanov J.T; Nurmatov K. Dj (Genius Journals, 2024)
In the article, the wide integration of advanced pedagogical technologies in higher education institutions in the field of architecture and construction, teaching in accordance with the abilities and capabilities of students, the introduction of a stratified approach, the use of advanced pedagogical technologies of education, factors affecting the formation of students as specialists, their mutual understanding motivations, the levels of competence that are important in the professional activity of our higher education pedagogues in the process of modern education are widely covered
Keywords: Construction; architecture; competence; student